2012
DOI: 10.1038/npp.2012.133
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Disruptions in Adolescents Exposed to Childhood Maltreatment and Vulnerability to Psychopathology

Abstract: Childhood maltreatment has been known to produce long-lasting impairments in behavioral, cognitive and social functioning, but their underlying mechanisms are not well-understood. A better understanding of their underlying mechanisms will aid in developing effective preventive interventions. Nineteen adolescent volunteers with no personal history of a psychiatric illness, but who were exposed to maltreatment during childhood, and 13 adolescent volunteers with no personal or family history of a psychiatric diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 46 publications
9
121
2
2
Order By: Relevance
“…Adverse events during early life are risk factors for the psychopathology and myelin development. 73,74 This also suggests that there are several critical periods during which environmental risk factors could impact the normal development of myelin. Indeed, transient changes in GSH levels induced by environmental insults during pre-, peri-and postnatal periods may have an impact on oligodendrocyte maturation, consequently affecting later structural connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events during early life are risk factors for the psychopathology and myelin development. 73,74 This also suggests that there are several critical periods during which environmental risk factors could impact the normal development of myelin. Indeed, transient changes in GSH levels induced by environmental insults during pre-, peri-and postnatal periods may have an impact on oligodendrocyte maturation, consequently affecting later structural connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous diffusion tensor imaging studies have found an association between early adversity, including a positive family history of major depressive disorder, parental verbal abuse, witnessing domestic violence, as well as childhood neglect and maltreatment, with lower fractional anisotropy values in several WM tracts during adolescence and young adulthood [47,48,49,50]. It should be noted, however, that these all represent severe forms of adversity and that these studies were most often conducted using participants with posttraumatic stress disorder, thereby making it difficult to distinguish the impact of early adversity from that of having posttraumatic stress disorder [51].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in neuroimaging have also allowed researchers to examine brain structures in depressed adults. Findings from these studies suggest that differences in brain function and structure have potential to predict depression in samples of high-risk individuals (Huang, Gundapuneedi, & Rao, 2012;Whalley et al, 2013).…”
Section: Risk For Depressionmentioning
confidence: 96%